2012
DOI: 10.1039/c1em10753d
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in urban aerosols collected with wetted-wall cyclonic samplers and seasonal fluctuations of live and culturable airborne bacteria

Abstract: Airborne transmission of bacterial pathogens from point sources (e.g., ranches, dairy waste treatment facilities) to areas of food production (farms) has been suspected. Determining the incidence, transport and viability of extremely low levels of pathogens require collection of high volumes of air and characterization of live bacteria from aerosols. We monitored the numbers of culturable bacteria in urban aerosols on 21 separate days during a 9 month period using high volume cyclonic samplers at an elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
(76 reference statements)
1
20
0
Order By: Relevance
“…Similar results have been obtained by Bowers et al [59], who have revealed that these are local sources of con tamination that play a major role in shaping the structure of bacterial community in the air, rather than temporary weather changes. Moreover, the results obtained by Ravva et al [40] and Bowers et al [59] are similar to the results of the present study and indicate that temperature is the only climate condition which influences bacterial community. The number of bacteria in cities has particularly high spa tial variability because microoganisms are often released from the linear emission sources (traffic routes) and area sources (sewage treatment plants).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results have been obtained by Bowers et al [59], who have revealed that these are local sources of con tamination that play a major role in shaping the structure of bacterial community in the air, rather than temporary weather changes. Moreover, the results obtained by Ravva et al [40] and Bowers et al [59] are similar to the results of the present study and indicate that temperature is the only climate condition which influences bacterial community. The number of bacteria in cities has particularly high spa tial variability because microoganisms are often released from the linear emission sources (traffic routes) and area sources (sewage treatment plants).…”
Section: Discussionsupporting
confidence: 81%
“…For example, Abdel Hameed et al [36] have noted 1800 CFU×m -3 of bacte ria in Wadi Hof near Cairo, Filipiak et al [37] as well as Bugaj ny et al [38] have noted 13 000 CFU×m -3 of me sophilic bacteria in Poznań in the summer, while Fang et al [33] have noted up to 22 000 CFU×m -3 of mesophilic bacteria in Beijing in the areas of high population density and heavy traffic. Bioaerosol in urban areas may contain as many as 1800 bacterial species, including those patho genic ones [34,39,40]. Moulds, an important microbial factor, substantially influ ence air quality.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Meanwhile, most waterfront microbial aerosol studies have been conducted in remote areas, 3,20,21 on a pier in open coastal waters, 22 or during a Saharan dust storm. 5 Moreover, these studies have generally focused on microbial aerosol concentrations and taxonomic identity but have not provided information about the end fate of the aerosols, including their fallout rates and viability upon deposition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Burkholderia spp. have been also isolated from various environmental sources, such as air 21,27,28) , soil 27,28) , and underground water 28,29) . Although most of the species in the genus Burkholderia are not pathologic, a few species are reported to be capable of causing infections 28) .…”
Section: Characteristics Of the Genera Of Airborne Bacteria In Railwamentioning
confidence: 99%